FAKTOR-FAKTOR KOMUNIKASI PENYEBAB MENURUNNYA TRADISI PERNIKAHAN DINI DI DESA KUNJOROWESI - Aisyul Jannah, Istishfa; Ningsih, Masnia; Lailiyah, Fatihatul (MAJAPAHIT POLICY, 2021)
Marriage is a physical and spiritual bond between a woman and a man which aims to form a happy and eternal familybased on God Almighty. Marriage at a young age is often referred to as early marriage. Like the phenomenon of one village in the districtMojokerto, namely Kunjorowesi Village, Ngoro District. This village is known as a remote village and many people have early marriages.This study aims to find out what are the communication factors that cause the decline in the tradition of early marriage in Kunjorowesi Village.This type of research is qualitative descriptive using case study methodology. This research resulted that the factorsThere are 3 reasons for the decline in early marriage in Kunjorowesi Village, namely perception, education, and environmental factors.